2012
DOI: 10.1177/0022034512463241
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Tooth Surfaces into Biologically Informative Caries Outcomes

Abstract: A supplemental appendix to this article is published electronically only at http://jdr.sagepub.com/supplemental. AbstrActDental caries affects most adults worldwide; however, the risk factors for dental caries do not necessarily exert their effects uniformly across all tooth surfaces. Instead, the actions of some risk factors may be limited to a subset of teeth/surfaces. Therefore, we used hierarchical clustering on tooth surface-level caries data for 1,068 Appalachian adults (ages 18-75 yrs) to group surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 15 publications
2
31
0
1
Order By: Relevance
“…This study has shown a substantial difference between the estimated power of multilevel models and classic regression analysis. Traditional regression analysis is known to overestimate the beneficial effects of interventions where clustering is present (Shaffer et al 2013;Masood and Reidpath 2014). In this analysis, we used fluoridation and frequency of brushing as examples of preventive measures: simple regression analysis ascribes a nearly 6 times greater beneficial effect to such interventions than 2-or 3-level multilevel analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown a substantial difference between the estimated power of multilevel models and classic regression analysis. Traditional regression analysis is known to overestimate the beneficial effects of interventions where clustering is present (Shaffer et al 2013;Masood and Reidpath 2014). In this analysis, we used fluoridation and frequency of brushing as examples of preventive measures: simple regression analysis ascribes a nearly 6 times greater beneficial effect to such interventions than 2-or 3-level multilevel analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the authors have shown that relevant categories were obtained by grouping surfaces based on caries co-occurrence. 27 This suggests that new models of phenotypes may capture more biologically informative patterns of tooth decay. This method indicated that bacteriolytic LYZL2 polymorphism was implicated in reducing caries on mandibular anterior tooth surfaces (incisors, canines, and first premolars).…”
Section: Compilation Of Reported Associations and Outcomesmentioning
confidence: 99%
“…Schematic illustration of varying tooth surface-level susceptibilities within a population group estimated to have relatively homogeneous (e.g., moderate) early childhood caries (ECC) risk, within the context of proximal causes and distal determinants of ECC development. Susceptibilities of tooth surfaces vary individually and may be grouped in biologically informative clusters (as discussed by Batchelor and Sheiham 2004;Shaffer et al 2013): case A depicts the dentition of a child with highly susceptible upper anterior smooth surfaces, B reflects high pit and fissure susceptibility, and C an overall uniform moderate susceptibility. Panels D and E illustrate the potential of using proximal measures of disease activity and a systems biology approach (discussed by Nyvad et al 2013) to ascertain precise estimates of disease propensity, which, for example, are likely to vary between upper anterior facial (D) and lower proximal [E] surfaces.…”
Section: Quantification and Time: The Missing Dimensionsmentioning
confidence: 99%
“…To inform tooth surface-specific predictions and decision making, analytical approaches should take into consideration both the varying propensity of lesion development between surfaces, the potentially informative clustering of surface-type groups, and the multilevel correlation of tooth surface-specific outcomes (Batchelor and Sheiham 2004;Divaris et al 2013;Shaffer et al 2013). For example, facial surfaces of maxillary anterior teeth are usually the first teeth to show evidence of the disease (Slayton 2015), whereas posterior approximal surfaces are at higher risk after the development of posterior contacts.…”
Section: Utilization Of Informative Heterogeneity Clustering and Comentioning
confidence: 99%